Relações entre consciência fonológica e vocabulário expressivo em crianças com desvio fonológico - Kaminski, Tassiana Isabel (2010)
This study aimed to investigate the occurrence of a relationship between phonological awareness and expressive vocabulary in children with normal language development and children with phonological disorders; it aimed also to compare the performance of children with normal language development to the one of children with phonological disorders; and to verify the influence of age in the performance of these abilities and in the relationship with each other. The sample was composed by seventy-four subjects divided in two groups: fifty in the control group (children with normal language development) and twenty-four in the study group (children with phonological disorders). These groups were subdivided according to the age of the subjects, and composing the control group: twelve children were five years old, twenty-seven were six years old and eleven were seven years old. In the study group: ten children were five years old, ten were six years old and four were seven years old. These subjects accomplished tests that evaluated their abilities in phonological awareness and expressive vocabulary. Initially, the performance of the two groups (control and study) was compared according to the age groups. Later, the subjects with phonological disorders were analyzed, in the three studied age groups in order to verify the existent correlations between phonological awareness and expressive vocabulary in these subjects, as well as the influence of age in these correlations and in the performance of the tests. According to the results, it can be concluded that the children of the study group that were five and seven years old obtained an inferior performance than the control group. The subjects six years old didn't present significant differences among the groups. The children five years old of the two groups presented difficulties in the same tasks, except in phoneme detection in word beginning. And the subjects six and seven years old of both groups showed difficulties just in expressive vocabulary. Also, there is a relationship among some abilities in phonological awareness and expressive vocabulary in children with phonological disorders, at different ages. The performances at these abilities get better as the children get older and the relationships are more intense when the children are younger; as they grow older, these abilities become more independent, reducing the number of correlations.